Pengaruh variasi temperatur kalsinasi terhadap karakteristik kalsium karbonat (CaCO3) dalam cangkang keong sawah (Pila ampullacea) yang terdapat di Kabupaten Pasaman (The effect of calcination temperature variations on the characteristics of calcium carbonate (CaCO3) in the shells of rice field snails (Pila ampullacea) found in Pasaman Regency) - Haryona Delvita; Djusmaini Djamas; - Ramli (PILLAR OF PHYSICS, 2015)
Snail paddy shells (Pila ampullacea) located in sub-discricts Simpang Alahan Mati Pasaman contain lots of calcium carbonate (CaCO3) that is widely utilized in the industry. On the research of test data was obtained in the form of deposits of calcium levels XRF shell snail paddy is 93,438%. Based on test data XRD is obtained that information due to the temperature of the calcination transformation phase aragonite to calcite phase. The rising temperature of calcination causes a change of the structure of CaCO3 from Hexagonal structure to Ortorhombik structure. The rising temperature of calcination, grain size CaCO3 anyone rise to a certain temperature and then decline, as the grain size increases from aragonite before dikalsinasi 83,872 nm became 106,302 nm dikalsinasi on temperature after 380 ̊C. While the phase of calcite have grain size on temperature 380 ̊C, 410 ̊C, 440 ̊C, 470 ̊C and 500 ̊C each 118,983 nm, 139,882 nm, 137,067 nm, 140,047 nm, and 63,533 nm